Prevalence, severity and risk factors of food allergy and food addiction among the people of Tangail district, Bangladesh - Ali, Md. Rayhan; Talukder, Ashraf Hossain; Molla, Md. Tarek; Alam, Nur- E-; Faruque, Md. Omar; Mohiuddin, A. K. M.; Mahmud, Shahin (International Journal Of Community Medicine And Public Health, 2020)
Background: Food allergy is an abnormal response of some particular foods triggered by the body’s immune system. Food addiction which generally shares a similar neurobiological and behavioral framework with substance addiction like foods. The aim of this study was to evaluate common food items responsible for food allergy along with food addiction among Bangladeshi people. Methods: A cross-sectional study among 699 participants in the Tangail district of Bangladesh was done to record the presence of food allergy and food addiction patterns. Chi-square tests and logistic regression analysis were performed to assess the association between different factors with food allergy and food addiction. Results: It was found that brinjal was the most frequent food item responsible for 28.3% of people’s food allergy. The main symptoms due to the food allergy were about 28.5% itching and 22.7% rash on the skin. According to this study, 50.4% of allergic patients took medicine and most of the allergic patients didn’t seek medical advice. A maximum of 72.8% of allergic patients also had an addiction to food. Street foods like jhalmuri, fried foods were the general food addicted items covering 34.9%. Food-addicted participants with food allergies reported significantly more problems with foods, where obesity and heart disease are recognized as clinical effects due to having higher amounts of fat and sugar to these foods. Conclusions: The study revealed some important determinants of food allergic and food addiction that will help to increase our knowledge for the greater interest of our health and further research.